History of Sufism in Nasaf Oasis (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article provides information about the formation of Sufism in Nasaf oasis, Sufi scholars, their life paths and works based on historical sources and research conducted in this direction in recent years.